Data on first record of brown morph banded langur (presbytis femoralis), leucistic dusky leaf monkey ( trachypithecus obscurus ) in Malaysia and review of morph diversity in langur (colobinae) - Najmuddin, Mohd Faudzir; Haris, Hidayah; Othman, Nursyuhada; Zahari, Fatin; Mohd-Ridwan, Abd Rahman; Md-Zain, Badrul Munir; Shahrool-Anuar, Rohani; Ayeb, Othman; Othman, Iqramullah; Abdul-Latiff, Muhammad Abu Bakar (Elsevier, 2020)
Morphism refer to polymorphic species, in which multiple colour variants coexist within a population. Morphism in pri- mates is common and langurs also exhibit certain character- istics of morphism, such as conspicuous natal coats. Banded langurs ( Presbytis femoralis ) and dusky leaf monkey ( Trachyp- ithecus obscurus ) exhibits the same characteristics of conspic- uous natal coats, but these coats are only limited to infants and changed when they reached adulthood. This article re- ports the first discovery of rare brown morph of two adult male banded langurs and one leucistic adult female dusky leaf monkey in Malaysia. We also conducted a systematic literature search to review the diversity of morphism in leaf monkey globally.